Human Rights and International Accountability of States in the Climate Crisis (Reconstruction of the Loss and Damage Principle Following the Latest Developments of the Cop) - Wagiman Wagiman; Adriansyah Halim (Jurnal Dialektika: Jurnal Ilmu Sosial, 2026)
The global climate crisis has transformed from an environmental issue into a fundamental human rights issue, directly impacting the rights to life, health, food, water, and a good and healthy environment. These impacts are disproportionately felt by developing countries, including the ASEAN region, despite their relatively small historical contribution to global emissions. In this context, the strengthening of the principle of loss and damage following the latest developments at the Conference of the Parties (COP) marks an effort by the international community to affirm the dimension of state international responsibility for loss and damage caused by climate change. However, this principle still faces conceptual, normative, and implementative problems within the international legal regime. This study aims to analyze the climate crisis as a human rights issue and reconstruct the principle of loss and damage within the framework of state international responsibility, by reviewing the comparative national legal arrangements of ASEAN countries and international law. The research method used is normative juridical with conceptual, legislative, and comparative approaches, through an analysis of international legal instruments, the latest COP policies, and national regulations in the ASEAN region. The results show that the strengthening of loss and damage after the latest COP reflects a paradigm shift in climate law from a voluntary commitment-based approach to a human rights-oriented climate justice approach. However, the absence of binding legal instruments weakens state accountability mechanisms. This research emphasizes the philosophical novelty of integrating human rights as the legitimate basis for state international accountability in the climate crisis. This research recommends strengthening binding international legal norms and harmonizing ASEAN national policies based on climate justice and human rights.